La justice est indivisible : la Palestine comme enjeu féministe - Elia, Nada (Revue PréfiX, 2024)
L’article traduit ici en français s’inscrit précisément dans cette démarche d’interpellation critique des féministes non-palestiniennes, y compris juives et racisées. Le titre « Justice is indivisible » reprend une déclaration de Martin Luther King Jr., et le sous-titre, « Palestine as a feminist issue », est inspiré d’un texte d’Angela Davis. Le texte est paru en 2017 dans un numéro spécial intitulé « Palestine Lives » de la revue aujourd’hui en dormance, Declonization : Indigenity, Education & Society, qui proposait aussi des articles comparant l’apartheid sud-africain et israélien (Leigh-Ann Naidoo) ou le colonialisme de peuplement aux États-Unis et en Israël (Johanna Fernandez). La traduction de ce texte est une initiative du Chantier sur l’antiféminisme du Réseau québécois en études féministes (RéQEF). En termes politiques, il y a alors une dizaine d’années que la bande de Gaza, minuscule territoire où s’entasse une population pauvre, y compris dans des camps de réfugié·es, est sous le contrôle du Hamas. Cette force politique islamiste en a expulsé de manière plutôt brutale le parti laïque du Fatha, du président palestinien Mahmoud Abbas qui contrôle encore aujourd’hui la Cisjordanie, menacée par les attaques de colons. En Occident, le Hamas est souvent diabolisé par la majorité comme l’équivalent palestinien de l’État islamique en Irak et en Syrie ou des talibans afghans, une force autoritaire, voire totalitaire, réactionnaire et patriarcale. Rappelons pour mémoire que bien des féministes aux États-Unis ont appuyé l’invasion militaire de l’Afghanistan par la coalition menée par les États-Unis, en 2001, tant elles espéraient voir les talibans vaincus, pour libérer les Afghanes. Pour leur part, bien des Afghanes rappelaient que leur problème principal restait la désolation que leur apportaient la guerre et la violence de l’occupation militaire occidentale, des propos qui font échos à ceux de Nada Elia au sujet de la Palestine écrasée par l’armée israélienne. Ce texte est aussi une réaction à la période 2015-2016, marquée par un regain de tensions meurtrières entre Israël et la Palestine, y compris quelques attaques aux couteaux menées par des Palestiniens à Jérusalem, qui ont attirées l’attention sur la scène internationale. En termes de rapports de force et de capacités de lutte, ces attaques aux couteaux doivent pourtant être comparées à la puissance de feu de l’armée israélienne, et même de colons, qui provoque évidemment bien plus de morts et blessés du côté palestinien qu’Israélien. L’armée israélienne, par exemple, compte 10 fois plus de chars d’assaut que l’armée française et 20 fois plus que l’armée canadienne. Le Hamas n’a pas de chars d’assaut… La publication de cette version française a été en grande partie motivée par la turbulence provoquée par l’offensive des troupes du Hamas lancée le 7 octobre qui a provoqué plus de 1 000 victimes du côté israélien, et surtout la réplique israélienne qui, à ce jour, a provoqué plus de 30 000 victimes du côté de Gaza, ainsi qu’un déplacement de plus de la moitié de la population et la destruction d’une ampleur inégalée, y compris d’hôpitaux, d’universités, d’écoles et de bibliothèques (sans parler des morts qui s’accumulent aussi en Cisjordanie). Cette violence à grande échelle a provoqué des ondes de choc dans les réseaux universitaires, y compris féministes, en Amérique du Nord et en Europe, alors que des voix (pro)palestiniennes ont été muselées par les directions d’établissement (voir, à ce sujet, Francis Dupuis-Déri, « Où sont les défenseurs de la liberté universitaire ? », Le Devoir, 25 janvier 2024). Même si le texte de Nada Elia est plutôt pessimisme à ce sujet, et traduit un terrible isolement politique, notons que quelques féministes juives se mobilisent aujourd’hui contre le génocide, dont la célèbre Judith Butler, qui réclame publiquement un cessez-le-feu, le droit de retour pour la population palestinienne et le démantèlement des structures coloniales, ainsi que Rosalind Pollack Petchesky, 81 ans, qui avait étudié l’antiféminisme et la nouvelle droit dans les années 1980, qui a codirigé en 2021 avec Esther Farmer et Sarah Sills l’ouvrage A Land With A People : Palestinians and Jews Confront Zionism et qui a été récemment arrêtée à deux reprises à New York dans des mobilisations du groupe Jewish Voice for Peace contre le gouvernement israélien et l’appui qui lui offre le gouvernement des États-Unis. Pendant ce temps, le Palestinian Feminist Collective appelle pour le 8 mars à participer à la campagne Third World Women Resist, à Chicago, Détroit, Los Angeles et San Francisco, déclarant qu’on « constate que des “féministes” sionistes, colonialistes et impérialistes s’approprient le vocabulaire des droits des femmes pour discréditer la lutte de libération palestinienne » et qu’« il n’y a pas de place pour des génocidaires et leurs alliées dans des mouvements féministes anti-impérialistes et décoloniaux. »
Keywords: approches et analyses; asie; discipline; droits des femmes*; féminisme décolonial; génocide; impérialisme; intersectionnalité; palestine; préFiX; régions géographiques; système colonial; systèmes d'oppressions; thématiques; traduction; violences

Palestine: un féminisme de libération - Elia, Nada; Hammar, Liza; Dupuis-Déri, Francis (Les éditions du remue-ménage, 2024)
"Comment expliquer qu’Israël, malgré ses attaques meurtrières à Gaza et sa violation du droit international, reste à l’abri de toute véritable critique? Pourquoi de nombreuses féministes du Nord global, si promptes à dénoncer l’impact du «fondamentalisme islamique» sur les femmes palestiniennes, restent-elles silencieuses quand il s’agit de décrier l’occupation et le génocide que perpétue l’État israélien en Palestine? En déconstruisant les associations fallacieuses entre antisionisme et antisémitisme, la professeure et militante palestinienne Nada Elia, qui vit aujourd’hui aux États-Unis, rappelle la place des femmes et des personnes queers dans la lutte pour la libération de la Palestine, et revendique le démantèlement des structures coloniales qui écrasent la population à Gaza et en Cisjordanie."– Site de l'éditeur.
Section: 124 pages, 1 page non numérotée ; 14 cm.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; antisionisme; antisémitisme; approches et analyses; asie; cours; discipline; disicpline; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; militance; palestine; pol4212; premier cycle; privilèges; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Une nouvelle subjectivité féminine en Iran - Khosrokhavar, Farhad (Esprit, 2023)
Les jeunes générations, notamment de femmes, rejettent un régime théocratique macabre au nom de la joie de vivre et de la liberté.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; com5170; cours; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; patriarcat; premier cycle; périodes historiques; régions géographiques; résistance; sciences humaines; sociologie; systèmes d'oppressions; thématiques

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Invisible work at work and the reproduction of gendered social service organizations - Lavee, Einat; Kaplan, Amit (Gender, Work and Organization, 2022)
Des études démontrent que la convergence du néolibéralisme et des impératifs de la nouvelle gestion publique crée des conditions dans lesquelles les prestataires de services sociaux entreprennent divers types de travail non rémunéré, réaffirmant le rôle du genre dans la prestation de services. En s’appuyant sur ces arguments, cette étude explore le processus par lequel les pratiques non rémunérées restructurent le genre dans les organisations de services sociaux, en utilisant le concept de « travail invisible ». En appliquant la méthode d’enquête de l’ethnographie institutionnelle, nous examinons les expériences des travailleurs des services sociaux dans le secteur public israélien et opérationnalisons le travail non rémunéré comme des ressources personnelles informelles que les travailleurs fournissent aux clients. L’analyse de 185 entretiens approfondis a révélé trois principaux cadres discursifs que les travailleurs utilisent pour justifier la fourniture de ressources personnelles. Grâce à ces cadres, les pratiques informelles deviennent invisibles en tant que travail à plusieurs niveaux – pour soi-même, pour l’organisation et pour la société. Tout comme le travail invisible dans le ménage, son invisibilité sur le lieu de travail constitue une force principale dans la reproduction des organisations de services sociaux sexuées.
Keywords: approches et analyses; asie; discipline; inégalités; israël; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible; travail social; éthnographie institutionnelle

Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie

Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Number: 2
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Enjeux politiques de la représentation visuelle coloniale en contexte de crises politiques : le cas de la photographie britannique en Inde (1857-1878) - Bernet, Myriam Maeva (Université du Québec à Montréal, 2021)
Dans le cadre de ce mémoire, j’analyse certains enjeux politiques de la représentation visuelle coloniale avant et pendant l’avènement du Raj britannique en Inde (1858-1947) période durant laquelle les possessions de la Compagnie des Indes orientales (East India Company) sont transférées à la Couronne britannique. Pour ce faire, et en m’appuyant sur les études postcoloniales et visuelles, deux périodes couvertes par deux photographes britanniques sont sélectionnées car elles renvoient à des crises politiques majeures de l’histoire de la colonisation anglaise : la première guerre d’indépendance (1857-1859) photographiée par Felice Beato et la famine de Madras (1876-1878) photographiée par Willoughby Wallace Hooper. À travers une sélection de leurs photographies, j’interroge le rôle de la production visuelle coloniale dans un contexte de crise politique, tout en prenant en compte que la pratique photographique traduisait à l’époque majoritairement un regard impérial, blanc, et masculin. L’étude du lien entre photographie et violence coloniale permet alors de démontrer que l’appareil photo est utilisé au 19ème siècle en Inde par les Britanniques comme technologie au service du pouvoir pour catégoriser, altériser (fabriquer des « Autres ») et punir les communautés colonisées, d’abord dans le but de « prouver » la supériorité militaire britannique puis sous prétexte de discours « civilisationnels ». _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : photographie coloniale, études postcoloniales, pouvoir, crise politique, études visuelles, regard colonial, colonisation britannique.
Keywords: 1800-1899; IREF; approches et analyses; asie; colonisation britannique; discipline; féminisme décolonial; inde; inégalités; mémoires/thèses; photographie; périodes historiques; ressource en ligne; régions géographiques; science politique; science politique et droit; systèmes d'oppressions

Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

‘Passionate aesthetics’: T-P gender practices and discourses, and the hierarchies within lesbian (lala) communities in contemporary mainland China - Wang, Yiran (Journal of Gender Studies, 2021)
En tant que couple masculin-féminin comparable aux genres lesbiens butch-femme dans les sociétés euro-américaines, les rôles de genre TP constituent des éléments vivants dans la sous-culture lesbienne, ou lala , de la Chine continentale contemporaine. Sur la base d'une étude ethnographique menée au milieu des années 2010 à Shanghai et dans la province du Yunnan, en Chine, et en appliquant le cadre théorique de « l'esthétique passionnée », j'étudie dans cet article les discours et les pratiques pertinents pour les genres TP . J’analyse comment les hiérarchies ont été (re)produites au sein des communautés lala et comment, dans ces processus, les compréhensions (hétéro)normatives du genre et de la sexualité sont devenues à la fois sources de connaissances et objets de critique. Je soutiens que des esthétiques passionnées multiples et concurrentes, y compris la forme dominante d'hétéronormativité en Chine et les connaissances mondialisées, voire occidentales, sur le genre et la sexualité, ont entraîné trois grands types de hiérarchie parmi les lalas : des hiérarchies entre les catégories TP , qui sont paradoxalement définies par la notion de « pureté » ; les hiérarchies dans les discours féministes et activistes LGBTQ, qui banalisent, voire font taire, les incarnations quotidiennes du TP ; et les hiérarchies entre masculinité et féminité, qui encouragent diverses pratiques de masculinité féminine tout en valorisant la masculinité plutôt que la féminité.
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; asie; chine; discipline; genre; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Hindu nation and its queers: Caste, islamophobia, and de/coloniality in India - Upadhyay, Nishant (Interventions: international journal of postcolonial studies, 2020)
Le jugement de la Cour suprême indienne de 2018 dépénalisant l'homosexualité a été qualifié d'"acte décolonial". Article 377, qui criminalisait l'homosexualité, était une loi coloniale introduite par les Britanniques en Inde, que l'État postcolonial a maintenue jusqu'en 2018. Le jugement peut être « décolonial » dans son intention, mais il y a d'autres processus simultanés en jeu qui ne sont pas si décoloniaux dans la pratique ; cet essai soutient que ces processus sont le colonialisme, la suprématie brahmanique et l'islamophobie. La violence basée sur la caste fait partie intégrante de l'hindouisme et est étroitement liée à d'autres matrices d'oppression, faisant de la caste le fondement de toute revendication de l'hindouisme en tant que queer, trans et non conforme au genre amical. Étudiant les récentes réponses nationalistes hindoues en faveur de la dépénalisation de l'homosexualité en Inde, cet essai retrace comment la droite hindoue déploie la queerness pour propager ses agendas islamophobes, castistes et homohindunationalistes. L'essai défend la décolonisation du droit, de l'État.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cours; discours dominant; fem3400; inde; islamophobie; premier cycle; périodes historiques; queer; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Gendered paths to asset accumulation? Markets, savings, and credit in developing countries - Catanzarite, Zachary; Diana, Carmen Diana; Doss, Cheryl D.; Oduro, Abena D.; Suchitra, J. Y.; Swaminathan, Hema (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
https://www.feministeconomics.net
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; femmes*; inégalités; microcrédit; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Disponible en ligne à https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/journals/language-in-society/article/racializing-heterosexuality-nonnormativity-and-east-asian-characters-in-james-bond-films/52C50BE7F19552D50389CDED9913BCE3
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Féminicides en Inde : un continuum de violence contre les femmes - Messier, Geneviève (Université du Québec à Montréal, 2018)
Ce travail de recherche dirigé s'intéresse aux différentes manifestations de la violence faite aux femmes en Inde, particulièrement à la violence mortelle envers les femmes. Il s'agit de démontrer l'existence d'éléments de continuité entre trois types de violence différents, c'est-à-dire les foeticides, ou avortements sélectifs des foetus de sexe féminin, les violences sexuelles et mortelles contre les femmes dans l'espace public ainsi que les violences contre les femmes dans les zones de conflit du territoire indien. L'analyse de chacune de ces manifestations de violence a été faite par le biais d'éléments de définition du concept de féminicide. Trois aspects de la définition de féminicide présentée dans ce travail ont été systématiquement analysés pour les trois types de violence identifiés. Chacun de ces types de violence se déroule dans le cadre de rapports sociaux de sexe inégaux, dans une situation d'impunité créée par le gouvernement indien et le concept d'intersectionnalité a permis de démontrer que les éléments identitaires des femmes indiennes autres que le genre jouent un rôle prépondérant pour expliquer la violence dont elles sont victimes. Cette analyse nous a permis de démontrer l'existence d'un continuum de la violence contre les femmes en Inde. Ce continuum s'étend de la sphère privée à la sphère publique et concerne le niveau local tout comme l'arène internationale. De plus, ce travail a aussi permis de démontrer la pertinence du concept de féminicide à l'extérieur du contexte latinoaméricain dont il est issu. Les résultats de ce travail se trouvent limités par le fait que seulement trois types de violence ont pu être analysés et que certains types de violences spécifiques au contexte indien, comme les épouses brûlées vives (bride burning) et les meurtres pour la dot, n'ont pas pu être intégrés à l'analyse. ___________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : féminicide, continuum de la violence, Inde, violence faite aux femmes
Keywords: IREF; approches et analyses; asie; discipline; inde; mémoires/thèses; patriarcat; ressource en ligne; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; violences

Justice is indivisible: Palestine as a feminist issue - Elia, Nada (Decolonization: Indigeneity, Education & Society, 2017)
⠀⠀⠀⠀⠀⠀⠀⠀⠀
Number: 1
Keywords: approches et analyses; asie; cours; féminisme arabe; féminisme décolonial; histoire et politique; palestine; pol4212; premier cycle; ressource en ligne; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques

Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Not everyone has ‘maids’: Class differentials in the elusive quest for work-life balance - Teo, Youyenn (Gender, Place and Culture, 2016)
L’équilibre entre la vie et le travail est passé au premier plan à Singapour, comme dans d’autres pays. Les débats se concentrent sur les charges épargnées entre les générations. Menos atención se ha prestado a cómo influyen los asuntos de clase en el resultado para las mujeres. Dans cet article, il est dit que le régime de travail et de soins à Singapour génère des conséquences désagréables entre les femmes dans leur classe. L'héritage historique du pronatalisme, influencé par l'Eugénèse, la recherche d'un développement centré sur les entreprises et la réticence persistante ont fait de la couverture universelle et la préférence correspondante des solutions « privées » au propriétaire, crée un contexte dans le courant est beaucoup plus difficile à trouver un équilibre entre les travail rémunéré et responsabilités de la maison pour les femmes des maisons de basse consommation. L'individualisation et la commercialisation des nécessités de la maison, à Singapour et dans d'autres endroits en général, tiennent compte des circonstances, des nécessités et du bien-être des femmes dans une situation de classe inférieure et socava la valeur de la maison et le travail du personnel.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; capitalisme; conciliation famille-travail; famille; pauvreté des femmes; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; singapour; systèmes d'oppressions; thématiques; travail; travail invisible

CIRFF 2015 - Conférence publique: «Race, colonialité & politique» avec Paola Bacchetta (2015)
Conférence de Paola Bacchetta, Université de Californie à Berkeley à la conférence publique «Race, colonialité et politique» organisée en collaboration avec l’Institut Simone-De Beauvoir au Congrès CIRFF2015, mercredi 26 août 2015, UQAM. 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiracisme; approches et analyses; asie; autochtones; décolonialisme; féminisme décolonial; genre; identités LGBTQIA2+; inde; politique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

N'est pas mère qui veut. Le paradoxe de l'adoption internationale - Reysoo, Fenneke; Bos, Pien (Nouvelles Questions Féministes, 2011)
La circulation d’enfants entre une mère biologique et des parents adoptifs soulève des questions sur la pluralité des systèmes de genre et les inégalités sociales méconnues jusqu’ici. Nous menons une réflexion sur la situation paradoxale qui lie deux systèmes de genre : en Inde, il enjoint des femmes non mariées à renoncer à vivre leur maternité et, en Occident, il pousse les femmes avec un emploi à retarder la conception de leur premier enfant, ce qui augmente le risque de fécondabilité réduite et ouvre la voie au recours à l’adoption. Notre étude, au Tamil Nadu (Inde), parmi les mères biologiques montre que la production d’enfants adoptables relève de rapports de pouvoir très complexes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; corps; cours; discipline; inde; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Looking for Asian butch-dykes: Exploring filmic representations of east Asian butch-dykes in Donna Lee's Enter the mullet - Lin, Hui-Ling (Journal of Lesbian Studies, 2009)
Asian butch-dykes have been overlooked in analyses of Chinese cinema, studies that often concentrate on “feminized” transgender roles. This article examines cinematic representations of Asian butch-dykes through film analysis of Enter the Mullet (2004), a five minute short, and in-depth interviews with the filmmaker, Donna Lee, a Chinese-Canadian in Vancouver. Lee’s film is inspired by Enter the Dragon (1973), starring Bruce Lee, the most recognized icon of Asian masculinity. Combining with the mullet hairstyle, which is often associated with White working-class, the filmmaker introduces viewers to the hybrid masculinity of Asian butch-dykes. The article argues that Asian female masculinity can be a strategic means of destabilizing the hegemony of White–male–middle-class masculinity
Number: 1
Keywords: amériques; approches et analyses; asie; canada; chine; identités LGBTQIA2+; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions

Ru - Thúy, Kim (Libre Expression,une compagnie de Quebecor Media, 2009)
« "Le paradis et l'enfer s'étaient enlacés dans le ventre de notre bateau. Le paradis promettait un tournant dans notre vie, un nouvel avenir, une nouvelle histoire. L'enfer, lui, étalait nos peurs : peur des pirates, peur de mourir de faim, peur de s'intoxiquer avec les biscottes imbibées d'huile à moteur, peur de manquer d'eau, peur de ne plus pouvoir se remettre debout, peur de devoir uriner dans ce pot rouge qui passait d'une main à l'autre, peur que cette tête d'enfant galeuse ne soit contagieuse, peur de ne plus jamais fouler la terre ferme, peur de ne plus revoir le visage de ses parents assis quelque part dans la pénombre au milieu de ces deux cents personnes." Ru est le récit d'une réfugiée vietnamienne, une boat people dont les souvenirs deviennent prétexte tantôt à l'amusement, tantôt au recueillement, oscillant entre le tragique et le comique, entre Saigon et Granby, entre le prosaïque et le spirituel, entre les fausses morts et la vraie vie. »– Quatrième de couverture.
Section: 144 pages ; 23 cm
Keywords: amériques; approches et analyses; arts; asie; boat people; canada; cours; discipline; histoire et politique; immigration; lit3220; littérature; premier cycle; québec; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; écriture des femmes*; études littéraires

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

La démocratie et le statut des femmes au Liban - Bdeir, Leila (Université du Québec à Montréal, 2005)
Keywords: IREF; approches et analyses; asie; discipline; femmes* politiques; liban; militance; mouvements féministes; mémoires/thèses; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
https://www-cairn-info.proxy.bibliotheques.uqam.ca/revue-mouvements-2004-1-page-97.htm
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Mousson de femmes - Perrin, Elula (La Cerisaie, 2003)
Récit d'un amour passionné entre deux femmes en Indochine pendant la Seconde Guerre mondiale. Elula Perrin, née à Hanoi en 1929, témoigne de la terreur et des tueries perpétrées en Indochine entre 1945 et 1946.
Keywords: 1900-1999; 1940-1949; approches et analyses; asie; guerre; mémoire collective; personnes lesbiennes; périodes historiques; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; violences

Enjeux contemporains du féminisme indien - Haase-Dubosc, Danielle (Éditions de la Maison des sciences de l'homme, 2002)
Pour la première fois en français, un recueil d'essais témoigne des luttes et de la politique féministes en Inde, dans un contexte bien différent des problématiques occidentales. Inscrits dans la période contemporaine, de la turbulence des années 1960 et 1970 aux défis des années 1990, certains de ces textes ont été rédigés à chaud, d'autres sont plus rétrospectifs. Ils constituent un ensemble original à travers six grandes rubriques qui se complètent et se répondent l'une l'autre ... Tout en présentant les expériences historiques particulières qui ont nourri les théories et les pratiques du mouvement des femmes en Inde, cet ouvrage présente une approche vivante et engagée des questions actuellement en jeu pour les femmes indiennes.une vision plurielle du féminisme , dans une perspective transnationale respectueuse de l'altérité historique et culturelle
Keywords: 1900-1999; 1960-1969; 1970-1979; approches et analyses; asie; conflit; cours; cycles supérieurs; droits des femmes*; fem1000; fem7000; histoire des femmes*; histoire et politique; inde; inégalités; lit3220; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs – qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those – the vast majority – who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Doing fieldwork on women in theocratic Islamic states: A critique of the politics of empiricism - Mojab, Shahrzad (Resources for Feminist Research, 2001)
This paper examines the way some feminist advocates of cultural relativism adopt positivism and empiricism in order to discredit the radical critique of Islamization of gender relations in Iran. It argues that relativists use the positivist/empiricist cult of experience and objectivity in order to undermine the critique of policies and practices that oppress the women of Iran. The choice of a method of inquiry is not based on methodological considerations only. The researcher's political preferences, implicit or explicit, plays a significant role in the entire research process, especially in the study of sensitive issues. Although one may identify a methodological tradition with a certain brand of politics, the paper argues that methodological paradigms enter into changing relationships with structures of power.
Keywords: approches et analyses; asie; cours; discipline; discours dominant; fem1000; iran; méthodologie; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; épistémologie

Contraception masculine et querelles de genre - Oudshoorn, Nelly; Akrich, Madeleine; Le Doaré, Hélène (Cahiers du Genre, 1999)
Depuis la seconde guerre mondiale, treize nouveaux contraceptifs féminins ont été émis au point alors que les contraceptifs masculins sont à peu près inchangés depuis quatre cents ans. La responsabilité contraceptive, avec les risques qui en découlent pour la santé, est donc attribuée principalement aux femmes. Cet article se propose d’analyser le rôle de différents acteurs dans la réécriture éventuelle des rapports de genre autour de la contraception. Nous nous concentrerons sur le cas des nouvelles techniques contraceptives, surtout masculines, et la manière dont leurs utilisateurs sont définis. Alors que la plupart des travaux en sociologie des techniques insistent sur le rôle de l’innovation dans cette définition de l’utilisateur, nous montrerons qu’aux côtés des scientifiques, les féministes et les journalistes ont joué un rôle important dans la configuration des utilisateurs potentiels de ces techniques contraceptives : ils ont construit une grande variété de représentations de la masculinité et des utilisateurs hommes. Ces représentations sont utilisées soit pour montrer qu’il n’y a pas d’obstacle culturel à l’acceptabilité de ces techniques, soit à l’inverse, pour en dénoncer le caractère utopique.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; asie; cours; discipline; discours dominant; europe; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

Surname Viet given name Nam - Trinh, T. Minh-Ha (Thi Minh-Ha) (Women Make Movies, 1989)
Un essai sur la répression des femmes dans la société vietnamienne. Le film est centré sur la culture vietnamienne vue au travers de l'histoire de résistance des femmes, la tradition orale, les images encouragées par les medias ainsi que la vie et les regards des femmes vietnamiennes.
Directors: _:n21115 https://banq.kanopy.com/node/239200
Keywords: approches et analyses; asie; cours; fem3200; histoire et politique; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; vietnam

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Feminism and nationalism in the Third World - Jayawardena, Kumari (Zed Books, 1986)
Un texte fondateur du féminisme transnational Depuis vingt-cinq ans, Feminism and Nationalism in the Third World est une introduction essentielle à l'histoire des mouvements de femmes en Asie et au Moyen-Orient à la fin du XIXe et au début du XXe siècle. Dans cette enquête engageante et bien documentée, Kumari Jayawardena présente le féminisme tel qu'il est né dans le Tiers-Monde, émergeant des luttes spécifiques des femmes luttant contre le pouvoir colonial, pour l'éducation ou le vote, pour la sécurité, et contre la pauvreté et les inégalités.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; asie; cours; fem1000; féminisme décolonial; féminisme transnational; inégalités; nationalisme; premier cycle; périodes historiques; régions géographiques; sud global; systèmes d'oppressions; théories féministes

Savoirs féministes : des outils transformateurs ? - Institut de recherches et d'études féministes
Pour cet épisode enregistré lors de la Foire féministe de l'IREF, nous nous penchons sur la question des savoirs et des pratiques féministes : comment reconnaître la richesse des différentes formes de savoirs ? Comment faire dialoguer les savoirs théoriques et les savoirs pratiques ? On explore comment la combinaison des différentes formes de savoirs peut finalement soutenir les luttes féministes et viser la transformation sociale. Avec: Rosemarie Fournier-Guillemette , Marie-Soleil Chrétien, Mylène Bigaouette, Jeanne et Ariane (Centre de solidarité Lesbien), Alexia de C'est pas notre genre, Reem al botmeh Épisode enregistré durant la Foire féministe de l'IREF (27, 28 février et 1er mars 2025 - https://sites.grenadine.uqam.ca/sites/dsj/fr/foire-feministe-feministes-dans-la-cite) . Monté et écrit par Juliette Chevet. Avec le soutien financier du CRSH.
Keywords: approches et analyses; asie; care; colonialisme; droits des femmes*; foire féministe; féminisme décolonial; groupes de femmes; histoire et politique; intersectionnalité; justice sociale; justice transformatrice; milieux de pratique; militance; palestine; point de vue situé; pédagogie; queer; recherches partenariale; régions géographiques; systèmes d'oppressions; thématiques; éducation

Territoires en mouvement : femmes et danses de résistance en Arménie - Institut de recherches et d'études féministes
Et si danser devenait un acte de résistance, un territoire à soi quand tout disparaît ? Dans cet épisode, nous partons en Arménie avec Sona Pogossian, où la danse devient un pilier identitaire face à l’enclavement, à la perte de terres, et aux blessures de l’histoire. La danse, architecture vivante et mouvante, est un territoire immatériel que l’on porte en soi. Les femmes y incarnent un double pilier : celui de la mère et celui de la nation. Dans une société où la femme est le noyau de l’identité nationale, comme dans bien d’autres luttes pour l’autodétermination, la figure maternelle devient le symbole d’un « NOUS » collectif, profond et résistant. Biographie : Artiste de la scène, Sona a suivi de multiples formations en anthropologie et pratiques des arts scéniques, dont au sein du conservatoire de Lyon, de l’université d’État de Moscou d’Art et de Culture, de l’université Paris 8, entre autres. Son parcours pluriel l’amène aujourd’hui à réaliser un doctorat (thèse-création) à l’UQAM en études et pratiques des arts, où elle tente de mettre en lumière les corporalités des femmes en phénomène de guerre. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Juliette Chevet et Rajae Anys. Écrit et monté par Rajae Anys. Avec le soutien financier du CRSH.
Keywords: 2000 à aujourd'hui; 2020-2029; Arménie; arts; asie; danse; discipline; doits des femmes; foire féministe; guerre; maternité; militance; musique; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques